Międzynarodowa współpraca jednostek samorządu lokalnego w zakresie turystki - Januszewska, Małgorzata; Nawrocka, Elżbieta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Co-operation among local authorities units is a good way for improving both quality and competitiveness of tourist economy and providing conditions for sustainable development of tourism in a given area. Cross-border co-operation extends opportunities for the development of regions situated along country borders and assists living conditions improvement for inhabitants of these areas. The objective of the hereby article is to present the scope (planes, area), intensity, barriers, as well as the assessment of co-operation, performed so far, between local authorities of communes and districts included in the Nisse Euroregion and perspectives for such co-operation development. The article also illustrates main domains of joint activities taken up by Polish, German and Czech communes and district related to tourism. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 57-65